A Dodecapeptide Selected by Phage Display as a Potential Theranostic Probe for Colon Cancers - Kwak, Moon Hwa; Yi, Gawon; Yang, Seung Mok; Choe, Younghee; Choi, Sangkee; Lee, Hye soo; Kim, Eunha; Lim, Yong beom; Na, Kun; Choi, Myung Gyu; Koo, Heebeom; Park, Jae Myung (Translational Oncology, 2020)
Aim: Colon cancer is one of the leading causes of cancer-related mortality. However, specific biomarkers for its diagnosis or treatment are not established well. Methods: We developed a colon-cancer specific peptide probe using phage display libraries. We validated the specificity of this probe to colon cancer cells with immunohistochemical staining and FACS analysis using one normal cell and five colon cancer cell lines. Results: This peptide probe maintained binding affinity even after serum incubation. For therapeutic applications, this peptide probe was conjugated to hematoporphyrin, a photosensitizer, which showed a significantly enhanced cellular uptake and high photodynamic effect to kill tumor cells. As another application, we made a nanoparticle modified from the peptide probe. It efficiently delivered SN-38, an anticancer drug, into tumor cells, and its tumor-targeting ability was observed in vivo after intravenous injection to the same xenograft model. Conclusion: The noble dodecapeptide probe can be a promising candidate for both colon tumor diagnosis and targeted drug delivery.